Reflexões sobre o sistema de avaliação da capes a partir do V Plano Nacional de Pós-graduação. (Revista de Educação Pública, 2012)
O presente artigo propõe uma reflexão sobre o modelo de avaliação da CAPES à luz do V Plano Nacional de Pós Graduação. O texto apresenta uma revisão das origens do modelo e, em seguida, relata as alterações efetuadas no período contemplado pelo referido plano. Por fim, discute os desafios que a CAPES enfrentará no futuro próximo, atrelados ao crescimento, à diversidade e assimetrias do sistema; à necessidade de conceituação da inserção social; à demanda por avaliações qualitativas e por articulações CAPES x SINAES e CAPES nova x velha, para assegurar a qualidade e a relevância da avaliação sob sua responsabilidade. Reflections on the CAPES Evaluation System from the perspective of the V National Plan for Graduate EducationAbstractThis article proposes to reflect on theCAPES evaluation model and its relationshipto the V National Plan for Graduate Education.The text presents a review of the originsof the model and, subsequently, relates thealterations effectuated during the time periodaddressed by the said plan. In its conclusion, itdiscusses the challenges that CAPES will facein the near future in order to assure the qualityand relevance of the evaluations for which it isresponsible. Such challenges are linked to thegrowth, diversity and asymmetry of the system;the need to conceptualize social insertion; thedemand for qualitative evaluations and for greaterarticulation between CAPES and SINAESand between the old and new CAPES.Keywords: Graduate studies. CAPES.Higher education evaluation.